PERBEDAAN FUNGSI KOGNITIF PADA PRA LANSIA DENGAN DIABETES MELITUS TIPE 2 DAN NON-DIABETES MELITUS DI RSUD PROF. DR M ALI HANAFIAH BATUSANGKAR - Rendri Bayu Hansah; Farhan Tomendra; Annisa Lidra Maribeth (Yayasan Nusantara Hasana Berdikari, 2024)
Damage to various organs, including the central nervous system, can lead to cerebrovascular diseases resulting in a decline in cognitive function, often unnoticed by type 2 diabetes mellitus (DM) patients. The decline in cognitive function can manifest in various forms, ranging from difficulty in remembering (forgetfulness), mild cognitive impairment (MCI), to dementia as the most severe clinical form. Early detection of cognitive function decline in the pre-elderly period is crucial for timely intervention or efforts to inhibit the progression of disorders. Early detection in the pre-elderly period is a step towards preventing cognitive function decline in the elderly. Objective of this research to determine the differences in cognitive function among pre-elderly patients with type 2 DM and non-DM at Prof. Dr. M. Ali Hanafiah Batusangkar Regional Hospital. The method used is a quantitative comparative approach with a cross-sectional design. The accessible population in the study consists of pre-elderly patients with type 2 DM and non-DM at Prof. Dr. M. Ali Hanafiah Batusangkar Regional Hospital, totaling 60 samples using consecutive sampling techniques. Univariate data analysis is presented in the form of frequency distribution, and bivariate analysis uses the chi-square test, with data processing using the IBM SPSS version 25.0 computerized program. Patients with DM experience more cognitive function disorders (96.7%). The statistical test using the chi-square test yielded a value of p=0.001 (p<0.05), indicating a difference in cognitive function between type 2 DM and non-DM patients at Prof. Dr. M. Ali Hanafiah Batusangkar Regional Hospital. Pre-elderly patients with type 2 DM are more likely to experience cognitive function disorders, whereas non-DM pre-elderly individuals mostly have normal cognitive function. There is a difference in cognitive function between type 2 DM and non-DM patients at Prof. Dr. M. Ali Hanafiah Batusangkar Regional Hospital